2008
DOI: 10.3168/jds.2007-0514
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Locomotion and Associated Conformation Traits of Holstein-Friesian Dairy Cows Managed in Different Housing Systems

Abstract: The objectives of this study were to determine the influence of housing on lameness-related linear and composite traits, and to estimate heritabilities of the traits and correlations among them. Data comprised 156,770 national type evaluation records of pedigreed first-lactation Holstein-Friesian cows that calved from 2000 through 2006 and were classified in different housing systems--cubicles, straw yards, slatted or loafing yards, and on pasture. Locomotion score (LOCO), rear leg, side view (RLS), foot angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 21 publications
6
20
0
3
Order By: Relevance
“…Campos et al (2012) showed that selection for final score should not increase milk production because of the low correlations between these characteristics. Onyiro and Brotherstone (2008) found that the breeding system affected scores for linear type, which is in accordance with the present results, as differences were observed among environments for type traits and milk production.…”
Section: Discussionsupporting
confidence: 92%
“…Campos et al (2012) showed that selection for final score should not increase milk production because of the low correlations between these characteristics. Onyiro and Brotherstone (2008) found that the breeding system affected scores for linear type, which is in accordance with the present results, as differences were observed among environments for type traits and milk production.…”
Section: Discussionsupporting
confidence: 92%
“…Buch et al (2011) reported moderate genetic correlations between mastitis with hoof diseases, sole ulcer and sole haemorrhage, in first-parity Swedish Red cows, which were 0.32 and 0.35, respectively, which were similar to estimates in this study (0.36 to 0.38). Other studies have found a relationship between locomotion with udder conformation traits, which are both type traits used as predictors of udder health and lameness (Boelling and Pollott 1998;Van Dorp et al, 2004;Onyiro and Brotherstone 2008). Results of Onyiro and Brotherstone (2008) implied that a well-fitted mammary system was associated with better locomotion, whereas cows with sagging or pendulous udders were more likely to suffer from lameness.…”
Section: Genetic Correlationsmentioning
confidence: 98%
“…Other studies have found a relationship between locomotion with udder conformation traits, which are both type traits used as predictors of udder health and lameness (Boelling and Pollott 1998;Van Dorp et al, 2004;Onyiro and Brotherstone 2008). Results of Onyiro and Brotherstone (2008) implied that a well-fitted mammary system was associated with better locomotion, whereas cows with sagging or pendulous udders were more likely to suffer from lameness. In addition, with increasing age the udder depth increases caused by higher milk yields of maturer cows and by loosening of the main tendon (Fascia trunci) that holds the udder, thus likely to impede locomotion.…”
Section: Genetic Correlationsmentioning
confidence: 98%
“…Firstly, cows in XE were housed all year round. In general, cows kept on pasture are likely to suffer fewer locomotion problems than those housed indoors (Gitau et al, 1996;Somers et al, 2003;Onyiro and Figure 3 Milk production curves for lame v. non-lame cows. Cows lame before 60 DIM ('), cows lame after 60 DIM (m) and cows never lame (E).…”
Section: Discussionmentioning
confidence: 99%
“…Cows lame before 60 DIM ('), cows lame after 60 DIM (m) and cows never lame (E). Brotherstone, 2008). Secondly, this group was fed higher levels of concentrate to support their higher milk yield.…”
Section: Discussionmentioning
confidence: 99%